2018
DOI: 10.1111/1756-185x.13377
|View full text |Cite
|
Sign up to set email alerts
|

Carotid ultrasound findings in rheumatoid arthritis and control subjects: A case‐control study

Abstract: It was confirmed that RA-patients have greater subclinical atherosclerosis represented in the carotid US measuring cIMT and CP as surrogates. RA-patients with subclinical atherosclerotic disease have more heterogeneous plaques characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 44 publications
2
6
0
Order By: Relevance
“…Wah-Suarez et al found that carotid plaque was over two times more present in RA than in controls [ 26 ], and Rueda-Gotor et al confirmed that the carotid ultrasound was more sensitive in detecting high cardiovascular risk axial spondylitis than the coronary artery calcification score [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wah-Suarez et al found that carotid plaque was over two times more present in RA than in controls [ 26 ], and Rueda-Gotor et al confirmed that the carotid ultrasound was more sensitive in detecting high cardiovascular risk axial spondylitis than the coronary artery calcification score [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review with meta-analysis showed a statistically significant increase in the risk of dementia among patients with RA compared with non-RA controls (Ungprasert et al, 2016). Bilateral carotid plaque was more than twice in RA than in controls (Wah-Suarez et al, 2019). In future studies, these four Drug-gene Interaction type: In inhibitor interactions, the drug binds to a target and decreases its expression or activity.…”
Section: Discussionmentioning
confidence: 99%
“…Dyslipidemia is an important comorbidity among patients with rheumatic diseases mainly because of its role in subclinical atherosclerosis development, increasing the cardiovascular risk and the prevalence of carotid plaque [ 75 , 76 ]. Although there is a lack of evidence about the behavior of blood lipid levels during the pandemic, some studies showed a trend of increased blood lipid levels when comparing before and after the lockdown in asymptomatic patients [ 77 ].…”
Section: Comorbidities During the Covid-19 Pandemicmentioning
confidence: 99%